トウキョウ カラ ナンキョク チイキ マデノ カイヨウ ジョウ デノ エートケン リュウシ ノウド ノ カンソク ジョホウ - 岩井, 邦中; イワイ, クニモト; 伊藤, 朋之; イトウ, トモユキ; 小野, 晃; オノ, アキラ; IWAI, Kunimoto; ITO, Tomoyuki; ONO, Akira (1979)
P(論文) 1976年11月25日から12月末にかけて,東京から南極地域まての海洋上におけるエートケン粒子の数濃度の連続測定を行った.オーストラリア西方の30°S付近のインド洋上において,100個/cm^3前後の低濃度を記録した.この低濃度は降水によるwashoutの結果である可能性がある.60°S～64°Sでは300～600個/cm^3で比較的安定して低濃度であった.64°S以南の海洋上,特にパックアイス中では,濃度に日変化があり,300個/cm^3から1800個/cm^3まで変化することがあった.このことは南極地域の夏の海洋上でエアソルが形成されていることを示す.北半球における最低値は,ミンダナオ島付近の10°Nの太平洋で観測された220個/cm^3であった. Continuous measurements of Aitken particle concentration were carried out by using an improved Pollak type automatic counter on board the FUJI between Tokyo and the Antarctic region from November 25 to the end of December, 1976. Very low concentrations of about 100 cm^<-3> were recorded in the Indian Ocean around 30゜S of the western coast of Australia. However, these low concentrations are considered to be the effect of washout by precipitation. Concentrations of 300 to 600 cm^<-3> were predominant between 60°S and 64°S. Concentrations over the sea in the south of 64゜S where pack ice was present were relatively high (300-2000 cm^<-3>) and diurnal variations of them were observed. Concentration of 220 cm^<-3>,the lowest in the northern hemisphere, was observed in the Pacific Ocean around 10゜N departmental bulletin paper